Analisis dan Perbaikan Set Up Time Dies untuk Minimalkan Waktu Henti Mesin Press dengan Pendekatan Lean Manufacturing Metode SMED di PT. Manufacturing Surabaya - Afirin, Ady Syamsul (SURYA TEKNIKA, 2025)
PT. Manufacturing Surabaya is a manufacturing company engaged in the production of clip components for automotive suspension systems. In carrying out its production activities, the company prioritizes high-quality products and good production productivity levels. The problem faced by the company is the high changeover setup time in the Production Division, specifically on the Press Machine. The changeover setup process of the dies on the press machine takes a long time during machine downtime. The setup changeover process reaches up to 3,126 seconds for a single changeover.This study aims to identify the factors causing the lengthy setup changeover process and to propose improvements using the Single Minutes Exchange of Dies (SMED) method. A fishbone diagram analysis indicates that the prolonged setup changeover time is caused by factors related to methods, manpower, machines, and environment.By implementing the SMED method, 21 internal activities were reduced to 16 internal activities. This change reduced the setup time from 3,126 seconds to 2,821 seconds, resulting in a 10% reduction in setup time and thereby improving production productivity.